2005
DOI: 10.1080/0300443042000270768
|View full text |Cite
|
Sign up to set email alerts
|

The effects of socioeconomic diversity on the language, cognitive and social–emotional development of children from low‐income backgrounds

Abstract: Previous studies on the influence of mixed groupings within preschool classrooms have indicated positive effects on children's development. This study extended earlier findings to determine the effects of socioeconomic diversity within the classroom on the language, cognitive and socialemotional development of preschool children of low-income backgrounds. Twenty-seven preschool children were enrolled in two classrooms in a private university's child development center. Twenty of the 27 enrolled were from low-i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 19 publications
0
6
0
1
Order By: Relevance
“…Included were case management services, child welfare, residential services, and financial assistance. Although the literature suggests that speech and language problems are seen in almost 75% of children with Downloaded by [National Pingtung University of Science and Technology] at 14:21 20 December 2014 behavioral problems and likely fuels their ongoing frustrations in school settings (Bagby et al, 2005;Benner et al, 2002), only one in five entered with any prior speech focused therapy and even fewer with occupational therapy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Included were case management services, child welfare, residential services, and financial assistance. Although the literature suggests that speech and language problems are seen in almost 75% of children with Downloaded by [National Pingtung University of Science and Technology] at 14:21 20 December 2014 behavioral problems and likely fuels their ongoing frustrations in school settings (Bagby et al, 2005;Benner et al, 2002), only one in five entered with any prior speech focused therapy and even fewer with occupational therapy.…”
Section: Discussionmentioning
confidence: 99%
“…Rudd, & Woods, 2005;Benner, Nelson, & Epstein, 2002).Benner et al found that 71% of those with SED had clinically significant problems in expressive, receptive, and pragmatic language. Downloaded by [National Pingtung University of Science and Technology] at 14:21 20 December 2014…”
mentioning
confidence: 96%
“…Studies have shown that children from high socioeconomic level have family environments that are more stimulating and conducive to learning than those of children from lower socio-economic levels (14)(15)(16) . In addition, the educational level of parents may also influence children's language development (14,17,18) .…”
Section: Discussionmentioning
confidence: 99%
“…Childhood vocabulary acquisition and language development vary widely as a result of individual differences in childhood environmental factors. Family socioeconomic status (SES) has been shown to be a major predictor of childhood language acquisition (Chaney, 1994; Bagby, Loretta, & Majka, 2005; Hoff, 2003; Hoff & Tian, 2005; Terrisse, Roberts, Palacio‐Quintin, & MacDonald, 1998). Lacroix et al (2001) observed 209 mother–child dyads of varying SES and found that children whose mothers were of a lower SES developed language more slowly during the first three years of life compared to those of children with higher SES mothers.…”
mentioning
confidence: 99%